2020
DOI: 10.1103/physrevresearch.2.012016
|View full text |Cite
|
Sign up to set email alerts
|

Turning off quantum duality

Abstract: We provide the first experimental confirmation of a three-way quantum coherence identity possessed by single pure-state photons. Our experimental results demonstrate that traditional wave-particle duality is specifically limited by this identity. As a consequence, we show that quantum duality itself can be amplified, attenuated, or turned completely off. In the Young double-slit context this quantum coherence identity is found to be directly relevant, and it supplies a rare quantitative backup for one of Bohr'… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 30 publications
(27 reference statements)
1
41
0
Order By: Relevance
“…Such correspondences were first established quantitatively by Wootters and Zurek [3] and then followed by many others [4][5][6][7][8][9][10] to achieve a duality inequality, V 2 + D 2 1, between single quantum object wave interference visibility V and particle location distinguishability D. Extended studies have explored more specific physical properties, in addition to coherence and localized position, by establishing quantitative connections of the duality inequality with photon polarization [11][12][13][14][15][16], single-particle quantum states [17], and alternative coherence measures [18,19]. Recently, it has been demonstrated that the wave-particle property is connected to the self-entanglement between path and all remaining intrinsic properties (degrees of freedom) of the same single quantum object, leading to a threeway complementary identity [20,21], V 2 + D 2 + C 2 = 1, with C being the usual entanglement measure concurrence [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such correspondences were first established quantitatively by Wootters and Zurek [3] and then followed by many others [4][5][6][7][8][9][10] to achieve a duality inequality, V 2 + D 2 1, between single quantum object wave interference visibility V and particle location distinguishability D. Extended studies have explored more specific physical properties, in addition to coherence and localized position, by establishing quantitative connections of the duality inequality with photon polarization [11][12][13][14][15][16], single-particle quantum states [17], and alternative coherence measures [18,19]. Recently, it has been demonstrated that the wave-particle property is connected to the self-entanglement between path and all remaining intrinsic properties (degrees of freedom) of the same single quantum object, leading to a threeway complementary identity [20,21], V 2 + D 2 + C 2 = 1, with C being the usual entanglement measure concurrence [22].…”
mentioning
confidence: 99%
“…Almost all these previous quantitative studies [11][12][13][14][15][16][17][18][19][20][21] employ the scenario of single-particle double-slit interference, where in the analysis the two slits are often assumed to be ideal point sources of a single quantum particle. Unfortunately, no source properties such as the slit width, roughness, etc., have been taken into account in duality analyses.…”
mentioning
confidence: 99%
“…Equation 12and 5are the same, because for pure, bipartite states, it holds C 2 + P 2 = 1 [28][29][30][31]. According to [13], Equation 12is the correct single-particle duality restriction. This is so, because the restriction D 2 + V 2 ≤ 1 allows that both D and V simultaneously increase or decrease, it being possible that D = V = 0.…”
Section: Entanglement As An Additional Coherencementioning
confidence: 99%
“…Let us now turn to another recent result in which wave-particle duality has been couched in quantum terms [13]. In this case, entanglement is addressed by writing (5) in the form [13,26]…”
Section: Entanglement As An Additional Coherencementioning
confidence: 99%
See 1 more Smart Citation